Effect of Nanosilica Addition and Temperature on Durability of Polymer Mortar in Seawater Environment - Septriansyah, Verinazul; Hasyim, Saloma; Nurjannah, Siti Aisyah (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
This study examines the effect of nano-silica addition and temperature variation on the durability of polymer mortar exposed to seawater. We investigated three specimen variations: polymer mortar without nanosilica (MP), polymer mortar with 0.4% nanosilica added (MP N 0.4%), and nanosilica polymer mortar with 85◦C heating (MP N 0.4% T 85◦C). Testing methods included cyclic and static immersion for 90 days in Tanjung Pandan, Bangka Belitung, followed by characterization through specific gravity, compressive strength, SEM (Scanning Electron Microscopy), FTIR (Fourier Transform Infrared Spectroscopy), and XRD (X-ray diffraction) analysis. Results showed that 0.4% nano-silica addition combined with 85◦C heating treatment significantly increased compressive strength to 51.78 MPa in cyclic immersion, compared to 38.17 MPa for standard polymer mortar. SEM analysis revealed a more compact microstructure with reduced porosity in nano-silica specimens, while FTIR confirmed the formation of new chemical bonds between the epoxy matrix and silica particles. XRD testing identified the presence of SiO2 crystalline phase and nano-silica distribution in amorphous form throughout the composite matrix. The optimized polymer mortar demonstrated superior durability in seawater environments, maintaining specific gravity stability and resistance to degradation after prolonged immersion, outperforming conventional cementitious materials in marine applications.